Active case finding and evaluation of IL-6 production among household contacts of pulmonary tuberculosis patients in a high disease setting - Chukwuanukwu, Rebecca C.; Onyenekwe, Charles C.; Anyabolu, Arthur E.; Onwunzo, Maria C.; C., Okonkwo Robert; O., Okeke Chizoba; O., Manafa Patrick; A., Eze Ukpai; M., Omigie Ngozi (International Journal of Research in Medical Sciences, 2021)
Background: Tuberculosis (TB) is a top infectious disease killer worldwide and remains a huge public health concern. However, most TB case findings are limited to self-referral (passive case finding), when individuals develop symptoms of TB. Only 15% of disease burden in Nigeria are reported. In view of this, it is important to assess the latent and active disease burden amongst HHC of TB patients suffering from pulmonary TB. In addition, it has been suggested that IL-6 levels could be used as a prognostic marker in exposed individuals. IL-6 levels were assessed in this cohort. Methods: A total of 205 subjects participated in this study, comprising 62 pulmonary TB index cases and 143 of their household contacts. Also, 54 apparently healthy subjects were recruited to serve as controls. Active case finding was performed amongst the HHC, using sputum and blood samples; they were tested for active TB. Blood samples were also collected for measuring IL-6 levels. Results: Findings reveal 6.3% previously undiagnosed active TB among the HHC of the TB patients and a significantly higher number of latently infected TB cases compared to the control population (p=0.0078). There were significant differences when comparing HIV co-infected index group to their HIV negative counterparts (P=0.032). Significantly different IL-6 levels were found among the study groups and sub-groups (p<0.0001), with significantly higher levels in TB mono-infection compared to in TB/HIV co-infection (p=0.031). Conclusions: These results demonstrate the importance of active TB case finding for TB control and the possible role of IL-6 as a diagnostic marker in TB control.